GAYA BAHASA DALAM LIRIK LAGU POP GAYA BAHASA DALAM LIRIK LAGU POPULER YANG DINYANYIKAN OLEH SYAHRINI: GAYA BAHASA DALAM LIRIK LAGU POPULER YANG DINYANYIKAN OLEH SYAHRINI - Etik Soetanty; M. Shoim Anwar (Universitas PGRI Adi Buana Surabaya, 2015)
The language style or known the Figure of Speech is an expression of feelings that have deep meaning for others. This research was conducted to look at the style of the language in the lyrics of popular songs by Syahrini. The analuses covered were stylistic repetition, alliteration, assonance, parallelism, “Simploke”, and redundancy. Analysis methods of this research used descriptive qualitative method. Based on the analysis of the lyrics of a popular song Syahrini explained that the style of repetitipn languange is a classification of words in a few times to amplify the pressure. We can see the lyrics of the songs, entitled: My Lovely, Aku Tak Biasa, Bohong, Kau Yang Memilih Aku, Semua Karena Cinta, Sesuatu, Cinta Tapi Gengsi, Pusing Setengah Mati, Aku Tak Biasa (Cover Alda) dan Kau Cetarkan Hatiku. While the other songs on the album are Tatapan Cinta, Kau Sengaja, Kau Sengaja, Sang Pencipta, Tak Terganti, Aku Pergi, Tak Memilih, Memilih Aku, Kau Bohong, Taubatlah Taubat, Ya Robbi, Cinta Terakhir, dan Jangan Memilih Aku. In the alliteration style is a kind of language style that is concrete use of the word tahat have teh begining of the same consonant. Analysis of language style of the lyrics songs by Syahrini is titled Kau Yang Memilih Aku, Sesuatu, Pusing Setengah Mati, dan Aku Tak Biasa (Cover Alda). Whereas in the others Syahrini song lyrics are entitled: Tatapan Cinta, Habislah Sudah, Sang Pencipta, Tak Terganti, Tak Memilih, Melewati Batas, Kau Bohong, Taubatlah Taubat, Ya Robbi, dan Jangan Memilih Aku. In stylistic assonance of vocal style is similar in the wording. In Syahrini song lyrics have stylistic analysis of a popular song titled: My Lovely, Aku Tak Biasa, Kau Yang Memilih Aku, Semua Karena Cinta, Sesuatu, Cinta Tapi Gengsi, dan Aku Tak Biasa (Cover Alda). According to other Syahrini song lyrics titled: Habislah Sudah, Sang Pencipta, Tak Terganti, Tak Memilih, Memilih Aku, Taubatlah Taubat, Cinta Terakhir, Suasana Dikota Santri. In the parallelism style is a confirmation of language pronunciation used to clarify a statement as the seriousness. In the Syahrini song lyrics have stylistic analysis of a popular song titled: Aku Tak Biasa, Bohong. “Simploke” is repeated word in the sentence at the beginning or end of the line or continued sentences. In the Syahrini song lyrics have stylistic analysis of a popular song titled: My Lovely, Aku Tak Biasa, Bohong, Kau Yang Memilih Aku, Semua Karena Cinta, Sesuatu, Cinta Tapi Gengsi, Pusing Setengah Mati, Aku Tak Biasa (Cover Alda), dan Kau Cetarkan Hatiku. While the lyrics of other songs titled: Kau Sengaja, Habislah Sudah, Tak Terganti, Aku Pergi, Melewati Batas, Memilih Aku, Kau Bohong, Taubatlah Taubat, Cinta Terakhir, Jangan Memilih Aku, dan Suasana Dikota Santri. Pleonasme is an excessive use of the word re-added the next sentence with a view to better of the meaning of the lyrics in a song. In the Syahrini song lyrics have stylistic analysis of a popular song entitled Bohong.